2019
DOI: 10.3390/molecules24112146
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Effects of Pentamidine Isethionate on Coagulation and Fibrinolysis

Abstract: Pentamidine is bis-oxybenzamidine-based antiprotozoal drug. The parenteral use of pentamidine appears to affect the processes of blood coagulation and/or fibrinolysis resulting in rare but potentially life-threatening blood clot formation. Pentamidine was also found to cause disseminated intravascular coagulation syndrome. To investigate the potential underlying molecular mechanism(s) of pentamidine’s effects on coagulation and fibrinolysis, we studied its effects on clotting times in normal and deficient huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…EA Inhibits the Trans-Glutamination Activity of Human FXIIIa. Inhibition of human FXIIIa by EA was evaluated by using a modi ed bi-substrate, uorescence-based trans-glutamination assay, as described earlier [18][19][20][21]. Dansylcadaverine and N,N-dimethyl-casein were used as two substrates, which upon FXIIIa-dependence conjugation show a marked increase in uorescence at 490-550 nm (λ EX = 360 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EA Inhibits the Trans-Glutamination Activity of Human FXIIIa. Inhibition of human FXIIIa by EA was evaluated by using a modi ed bi-substrate, uorescence-based trans-glutamination assay, as described earlier [18][19][20][21]. Dansylcadaverine and N,N-dimethyl-casein were used as two substrates, which upon FXIIIa-dependence conjugation show a marked increase in uorescence at 490-550 nm (λ EX = 360 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Direct Inhibition of Human FXIIIa by EA. To evaluate the effect of EA on human FXIIIa, a bi-substrate, uorescencebased trans-glutamination assay was performed as we reported previously [18][19][20]. Generally, 1 µL of EA was diluted with 87 µL of pH 7.4 buffer (50 mM Tris-HCl, 1mM CaCl 2 , 100 mM NaCl, and 2 mg/mL N,Ndimethylcasein) and 5 µL dithiothreitol (20 mM) at 37°C followed by the addition of 2 µL of human FXIIIa (0.3 µM) and incubation for 10 min.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of different concentrations of inhibitor 1 on APTT and PT of normal human plasma was measured ( Table 3 and Figure 4), as described in earlier studies. [54,55,60,61] Results indicated that inhibitor 1 concentrationdependently prolonged APTT but not PT over the concentration range of 0-470 μM. Figure 4A shows the effect of anti-FXIa monoclonal antibody on the clotting times.…”
Section: Effect Of Inhibitor 1 On Clotting Times Of Normal and Fxi Dementioning
confidence: 97%
“…Pentamidine, an aromatic diamidine, is used to treat first-stage (haemolymphatic stage) T. gambiense HAT (Denise and Barrett, 2001; Barrett et al ., 2007; Baker et al ., 2013). This compound binds nucleic acids with high affinity, leading to accumulation by, and ultimately destruction of, the kinetoplast (Mathis et al ., 2006; Baker et al ., 2013; Gould and Schnaufer, 2014; Al-Horani et al ., 2019; Kennedy and Rodgers, 2019). However, pentamidine is unable to reach the central nervous system (CNS), in part due to its high affinity interactions with serum proteins, charge and relatively high retention in tissues and is therefore ineffective for the treatment of second-stage meningoencephalic HAT (Barrett et al ., 2007; Maclean et al ., 2012).…”
Section: Tbaqp2 and Multidrug Resistancementioning
confidence: 99%